CONCENTRATION OF JURISDICTION – IS FUNCTIONALITY OF JUDICIARY BECOMING AN OBSTACLE TO ACCESS TO JUSTICE? (EU and comparative law issues and challenges series (ECLIC), 2019)
Matters of jurisdiction seem to be among aspects of judicial cooperation in civil and commercial matters in which so far most regulatory activity of the European union (hereinafter: EU) has been undertaken. Upon close examination of the rules on jurisdiction of courts in civil and commercial matters in the existing legal framework at EU level, it becomes obvious that they contain the same principle of territoriality. At the same time, in the course of modernization both at the national and EU level it seems that the principle of functionality is becoming more dominant. A question whether it is justified to depart from rules on jurisdiction based on the principle of territoriality and confer jurisdiction on a court other than that of the defendant’s domicile based on the principle of functionality in a cross-border case has arisen recently in joined cases C-400/13 and C-408/13. Within the context of a rather ambiguous view the CJEU took in its decision in the aforementioned cases, the paper examines if enhancing functionality through concentration of jurisdiction will eventually become an advantage or obstacle to access to justice. The analysis includes presentation and comparison of provisions on jurisdiction in cross-border cases based on the principle of territoriality and functionality respectively in several EU legal instruments regulating private international law and civil procedure matters. The paper attempts to draw attention to models of achieving procedural efficiency in different fields of EU’s activity, such as enhancing consumer protection or introducing cross-border collective redress.